Norms of scientific rationality and prospects of academic discourse (to the 100th anniversary of Belarusian State University) - Sayganova, Veronika S.; Belyatskaya, Elizaveta V.; Mozalevskaya, Daniela A. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article discusses the main approaches to the study of the norms of scientific rationality in the context of promising areas of academic discourse. The academic discourse of the university is impossible without reliance on science and adherence to the norms of scientific rationality. The heuristic potential of synergetic, plastic, sociocognitive and communicative models of rationality is emphasised. The guidelines of a new type of rationality and promising directions of scientific research are substantiated. A new type of rationality opens itself up in modern times as a subject-subjective rationality, expanding the possibilities for interpreting rationality through discursive practices, communicative characteristics, academic norms and rules. The university acts as a significant subject of interaction in the communicative sphere of modern culture and is the bearer of scientific rationality, expressed in objective stable characteristics of scientific and educational activities, as well as in openness to new dimensions and innovations of the modern world.